Infra-inguinal arterial bypass procedures at Groote Schuur Hospital, 1977-1983 : analysis and evaluation of results - Bass, David Hyman (Department of Surgery, 2017)
Infra-inguinal arterial bypass is becoming increasingly popular as a means of alleviating incapacitating symptoms of atherosclerosis and other progressive diseases affecting the arteries of the lower limb. The role of this procedure in limb salvage is controversial but an aggressive attitude is emerging from many centres. It is accepted that the majority of atherosclerotic patients have a short life expectancy but reconstructive vascular surgery has an important role to play in improving their quality of life. Progress in infra-inguinal bypass surgery has centred mainly on the development of synthetic grafts but the perfonnance of autologous saphenous vein has not been bettered in terms of longterm results and cost-effectivity. The initial experience of infra-inguinal bypass at Groote Schuur Hospital, Cape Town, is examined retrospectively with the objective of demonstrating the possible influence of patient factors and specific surgical practices on the outcome of results.